The study of the homogeneity management of nursing quality within members of the tightly-knit medical alliance (紧密型医联体内护理同质化管理与效果) - ZHANG Yuhong (张育红); YAN Meiqiong (颜美琼) (中西医结合护理)
Objective To evaluate the homogeneity management of nursing quality within members of the tightly-knit medical alliance. Methods From September, 2017 to September 2020, Zhongshan Hospital of Fudan University implemented unified training, standard and quality in order to achieve nursing homogeneity management through resource sharing and information exchanging in the Zhongshan-Xiamen Hospital, the nursing quality was continuously improved by multiple unannounced inspections annually. Results The grading nursing care , ward management, first aid items, disinfection-isolation and nursing documents after the implementation of homogeneity management were significantly better than pre-homogeneity management (P<0. 01), and so did the outcomes of assessment on clinical nursing skills (P<0. 01). Conclusion Within members of the tightly-knit medical alliance, the nursing homogeneity management can effectively promote nursing management and personnel quality, thus enhance nursing quality and patient satisfaction, thus the compact medical consortium can provide the best care for the patients. (目的 探讨紧密型医联体单位实施护理质量同质化管理的有效措施和效果分析。方法 从2017年9月—2020年9月, 复旦大学附属中山医院通过资源共享、信息互联互通, 对紧密型医联体复旦大学附属中山医院厦门医院采取统一培训、统一标准、统一质量, 实施护理同质化管理。结果 实施同质化管理后的分级护理、病区管理、急救物品、消毒隔离、护理文件书写指标质量分提升明显(P<0. 01)。实施同质化管理后, 护士临床实践能力考核评分优于管理前(P<0. 01)。结论 紧密型医联体模式通过资源共享、信息互联互通, 可有效实施护理标准同质化管理, 提升医联体护理质量水平和人员素质, 从而为患者提供优质服务, 为医院护理发展提供基础。)